A concept analysis of patient‐centred nursing in the intensive care unit. (27th February 2015) - Jakimowicz, Samantha; Perry, Lin
Abstract Aim To report an analysis of the concept of patient‐centred nursing in the context of intensive care. Background Clarification of patient‐centred nursing in the intensive care unit is important because consensus definition of this concept is lacking. The severely compromised physiological state of these people and the sequelae of this differentiate patient‐centred nursing in intensive care from that occurring in other hospital settings. While the broad concept has been analysed, it has not been examined in the context of intensive care. Design Concept analysis. Data sources CINAHL, PsycINFO, Medline and PubMed databases (2000–2014) were searched. Peer‐reviewed papers were identified and reference lists of relevant articles searched. Methods Walker and Avant's eight‐stage approach was used. Results Patient‐centred nursing in the intensive care unit incorporates antecedents of a physiologically compromised patient requiring biomedical intervention, a professional and competent nurse and organizational support. The concept's defining attributes entail maintenance of patient identity by a compassionate and professional nurse exercising biomedical expertise. Consequences include patient satisfaction, positive patient experience, nurse job satisfaction and better nurse workforce retention. Conclusion Patient‐centred nursing in intensive care is differentiated from other healthcare areas by the particular characteristics of critically ill patients, the critical care environment and the challenging bio‐psycho‐social demands made on intensive care nurses. Effective patient‐centred nursing in this environment promotes beneficial outcomes for patients, nurses and healthcare service. Decision‐makers and policymakers should support critical care nurses in this challenging role, to maintain delivery of patient‐centred nursing and grow an effective nursing workforce.